Insight Into Metabolic Versatility of an Aromatic Compounds-Degrading Arthrobacter sp. YC-RL1 - Ren, Lei; Jia, Yang; Zhang, Rui; Lin, Zhong; Zhen, Zhen; Hu, Hanqiao; Yan, Yanchun (Frontiers in Microbiology, 2018)
The genus Arthrobacter is ubiquitously distributed in different natural environments. Many xenobiotic-degrading Arthrobacter strains have been isolated and described; however, few have been systematically characterized with regard to multiple interrelated metabolic pathways and the genes that encode them. In this study, the biodegradability of seven aromatic compounds by Arthrobacter sp. YC-RL1 was investigated. Strain YC-RL1 could efficiently degrade p-xylene (PX), naphthalene, phenanthrene, biphenyl, p-nitrophenol (PNP) and bisphenol A (BPA) under both separated and mixed conditions. Based on the detected metabolic intermediates, metabolic pathways of naphthalene, biphenyl, PNP and BPA were proposed, which indicated that strain YC-RL1 harbors systematic metabolic pathways towards aromatic compounds. Further, genomic analysis uncovered part of genes involved in the proposed pathways. Both intradiol and extradiol ring-cleavage dioxygenase genes were identified in the genome of strain YC-RL1. Meanwhile, gene clusters predicted to encode the degradation of biphenyl (bph), para-substituted phenols (npd) and protocatechuate (pca) were identified, and bphA1A2BCD was proposed to be a novel biphenyl-degrading gene cluster. The complete metabolic pathway of biphenyl was deduced via intermediates and functional gene analysis (bph and pca gene clusters). One of the these genes encoding ring-cleavage dioxygenase in bph gene cluster, a predicted 2, 3-dihydroxybiphenyl 1, 2-dioxygenase (BphC) gene, was cloned and its activity was confirmed by heterologous expression. This work systematically illuminated the metabolic versatility of aromatic compounds in strain YC-RL1 via the combination of metabolites identification, genomics analysis and laboratory experiments. These results suggested that strain YC-RL1 might be a promising candidate for the bioremediation of aromatic compounds pollution sites.